2010
DOI: 10.1002/cphc.200900628
|View full text |Cite
|
Sign up to set email alerts
|

High Electrocatalytic Activity of Pt–Pd Binary Spherocrystals Chemically Assembled in Vertically Aligned TiO2 Nanotubes

Abstract: To obtain noble metal catalysts with high efficiency, long-term stability, and poison resistance, Pt and Pd are assembled in highly ordered and vertically aligned TiO(2) nanotubes (NTs) by means of the pulsed-current deposition (PCD) method with assistance of ultrasonication (UC). Here, Pd serves as a dispersant which prevents agglomeration of Pt. Thus Pt-Pd binary catalysts are embed into TiO(2) NTs array under UC in sunken patterns of composite spherocrystals (Sps). Owing to this synthesis method and restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 66 publications
(69 reference statements)
1
12
0
Order By: Relevance
“…From these CA experiments, the turnover number (TON) was also calculated to understand the difference in electrocatalytic activity and stability of electrocatalyst. From the steady-state current density, TON, expressed as molecules per site, is calculated from eq 5: 44 = × × i nF TON (6.02 10 )…”
Section: ■ Introductionmentioning
confidence: 99%
“…From these CA experiments, the turnover number (TON) was also calculated to understand the difference in electrocatalytic activity and stability of electrocatalyst. From the steady-state current density, TON, expressed as molecules per site, is calculated from eq 5: 44 = × × i nF TON (6.02 10 )…”
Section: ■ Introductionmentioning
confidence: 99%
“…First, the TiO 2 NTs substrate was prepared by anodic oxidation on which the crystalline-seed-assisted hydrothermal method was adopted to construct SC ZnO according to the literature with certain modification. A 5 mM Zn(CH 3 COO) 2 ethanol solution was spin-coated on TiO 2 NTs several times, and then, a dense seed layer can be attained via 350 °C heat treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Such vertically aligned nanotubes of Ti can be easily fabricated by simple electrochemical anodization of planar Ti. 34,35 Zhao et al 36 discussed in detail the role of vertically aligned TiNT as support material for electrocatalytic application. They reported that nanotubular metallic support provides favorable physicochemical stability and avoids catalyst loss and poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…37 To synthesize Pt nanoparticle electrode with TiNT array support, several methods have been adopted. 36,38,39 The major drawback in most of the methods other than sputter coating is the aggregation of Pt particle resulting in reduced catalytic activity. 36,40 Wet impregnation is the most widely used method for synthesizing supported Pt catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation